212k views
4 votes
12 + 2x - x = 9x + 6


I need help!!

1 Answer

6 votes

Answer:

3/4

Explanation:

Start by simplifying (2x-x) to just (x)

The equation should now look like this: 12+x=9x-6

Now subtract the x on the left side of the equation on both sides.

The equation should now look like this: 12=8x-6

Now add 6 on both sides

The equation should now look like this: 6=8x

To get x by itself you must divide 8 on both sides

The equation should now look like this 6/8=x

Don't forget to simplify your fractions!

6/8 simplified is 3/4, giving you the answer 3/4

User Mgrueter
by
6.1k points